Social capital and firm operational performance: The mediating roles of knowledge sharingh - Minh Tri Ha (Cogent Business & Management, 2021)
Personal or private relationships between leaders of construction firms and government officials are critical to a firm's market success because they provide access to valuable information that their competitors do not. This study was carried out to investigate the associations between social capital dimensions, the sharing of knowledge and firm operational performance of small and medium-sized enterprises (SMEs) in the construction sector. Our study utilised a questionnaire-based survey design to gather online data using a convenience sampling method. To test the hypotheses, data obtained from 346 SMEs were analysed using structural equation modelling. Overall, other than the connection between structural social capital and explicit knowledge sharing, all social capital dimensions had a positive impact on both explicit and tacit knowledge sharing. Furthermore, explicit and tacit knowledge sharing positively influenced firm operational performance. Surprisingly, only cognitive social capital dimension was found to affect operational performance directly. Our study offers several practical implications regarding how firms can enhance improved operational performance in relation to advocating social capital dimensions and the sharing of knowledge.
Keywords: 650; construction; knowledge sharing; operational performance; SMEs; social capital; Vietnam